The Use of Biology Textbook based on Collaborative Learning Model to Improve Scientific Literacy Skill - Virlya Citra Dewi; Endang Susantini; Sri Poedjiastoeti (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
Scientific literacy skills are important skills taught to prepare students for the 21-st century learning era. Textbook based on collaborative learning model can be an alternative to improving students' scientific literacy skills. The purpose of the study was to describe scientific literacy skills and student responses through the use of biology textbook based on collaborative learning model. The type of research used is descriptive quantitative research with one group pretest-posttest research design. The instruments used are scientific literacy skills tests and response questionnaire sheets. The N-gain score, a paired sample t-test, and the results of the students' responses were used to analyze the data. The results showed that the value of the science literacy skills test increased with an N gain of 0.67, sig 0.05, and 95% of students responded positively. These results indicate that textbook based on collaborative learning model is effectively used to train students' scientific literacy skills and can be tested widely.